2012
DOI: 10.1016/j.jtcvs.2012.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Robotically assisted mitral valve replacement

Abstract: Robotically assisted mitral valve replacement can be performed safely in patients with isolated mitral valve stenosis, and surgical results are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 10 publications
0
26
1
1
Order By: Relevance
“…In this series, five mitral valves were considered irreparable and replacement was performed. The benefits of robotic mitral valve replacement include smaller thoracotomy, better visualization and exposure of the valve, and easier suture handling in difficult anatomy (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, five mitral valves were considered irreparable and replacement was performed. The benefits of robotic mitral valve replacement include smaller thoracotomy, better visualization and exposure of the valve, and easier suture handling in difficult anatomy (11).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical access for ASD repair was similar to the approach used in robotic-assisted mitral valve surgery (11). In ASD repair, the right atrial chamber was accessed after isolation of the superior and inferior venae cavae.…”
Section: Correction Of Atrial Septal Defectmentioning
confidence: 99%
“…Since right atriotomy through the right chest had provided us with excellent and reliable exposure of the right heart and the left atrium for robotic repair of ASD [3], VSD [2,5], mitral valve [6], atrial mass [7,8], and PS (data not published), the initial attempt of novel robotic repair of AVSD via right atriotomy was made with success. The long operation time was thought to be a shortcoming of robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the technique, our dissection of the intercostal spaces is minimal and corresponding for the size of the incision in the skin, and the removal of the intercostal space is limited, avoiding trauma to the ribs and thereby decreasing postoperative pain. Some centers advocate the use of video or robotic systems for performing these surgeries [4,9,11]. In Brazil, Poffo et al [11] reported their experience of minimally invasive surgeries with the aid of video, including being performed a pioneering procedure by periareolar access.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgeries refer to a variety of infusion techniques and visualization, allowing to perform surgeries with smaller incisions [4][5][6][7]. From the early 1990s, several authors began to advocate the use of these techniques, which have become the preferred approach for repair and valve replacement in a few specialized centers [1].…”
Section: Introductionmentioning
confidence: 99%